Risk Assessment Interviews: Exploring the Perspectives of Psychologists and Indeterminate Sentenced Prisoners in the United Kingdom. (August 2018) - Shingler, Jo; Sonnenberg, Stefanie J.; Needs, Adrian
This study explores the forensic risk assessment interview from the perspectives of qualified prison-based psychologists and indeterminate sentenced prisoners in the United Kingdom. It focuses on the psychologist–prisoner relationship in the interview context. Twenty-one in-depth individual interviews were conducted with psychologists and prisoners and analysed using Grounded Theory methods. The analysis identified the following categories reflecting participants' descriptions of risk assessment interviews: "Emphasising Clarity and Transparency, " "Collaborative Engagement, " "Making a Respectful, Boundaried yet Human Connection, " "Respecting Individuality, " and "Having a Purposeful Conversation." Analysis demonstrated that these categories of meaning reflected the broader notion of risk assessment interviewing as "A Difficult Balancing Act." The views of prisoners and psychologists about the risk assessment interview were remarkably similar and provide some direction and guidance for practitioners navigating this challenging but essential aspect of forensic psychological work.